2018
DOI: 10.5539/jel.v7n5p76
|View full text |Cite
|
Sign up to set email alerts
|

Schools as Professional Learning Communities

Abstract: The main objectives in building professional learning communities are to improve teachers' professionalism and well-being, and create positive impacts on student learning. It is a question of changing the school culture. The main objective of this quantitative study was to investigate the maturity level of thirteen Finnish schools as professional learning communities from the perspectives of school culture, leadership, teaching, and professional development. The participants' perceptions indicated a culture of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
47
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 44 publications
6
47
0
2
Order By: Relevance
“…Although there is relatively scarce amount of recent research in this area focused on the issue of musical giftedness of lower primary school students (Bačlija Sušić & Svalina, 2018;Sukop et al, 2016;Zalar & Sicherl-Kafol, 2015), emphasizing the importance and possibilities of improving work with musically gifted children in the lower grades of elementary school, Lelea (2014) considers that "identification and encouragement of musical giftedness is one of the primary goals of modern education that presents a challenge for research" (Lelea, 2014, p. 61). The positive culture of the school is also an important factor in identifying musically gifted students as it supports the professional cooperation of teachers with other staff members (Antinluoma, Ilomäki et al, 2018), therefore in accordance with this, the cooperation of teachers with music teachers and members of the professional team is also expected. Given that quality music education primarily depends on quality teaching and quality collaboration and support, it is important to provide the necessary music and professional development for primary school teachers (Clarke, 2007).…”
Section: Introductionmentioning
confidence: 83%
“…Although there is relatively scarce amount of recent research in this area focused on the issue of musical giftedness of lower primary school students (Bačlija Sušić & Svalina, 2018;Sukop et al, 2016;Zalar & Sicherl-Kafol, 2015), emphasizing the importance and possibilities of improving work with musically gifted children in the lower grades of elementary school, Lelea (2014) considers that "identification and encouragement of musical giftedness is one of the primary goals of modern education that presents a challenge for research" (Lelea, 2014, p. 61). The positive culture of the school is also an important factor in identifying musically gifted students as it supports the professional cooperation of teachers with other staff members (Antinluoma, Ilomäki et al, 2018), therefore in accordance with this, the cooperation of teachers with music teachers and members of the professional team is also expected. Given that quality music education primarily depends on quality teaching and quality collaboration and support, it is important to provide the necessary music and professional development for primary school teachers (Clarke, 2007).…”
Section: Introductionmentioning
confidence: 83%
“…Komponen kedua di dalam model kepimpinan distributif Spillane (2006) adalah pengikut yang merujuk kepada guru-guru di sekolah (Spillane, 2006) atau anggota komuniti pembelajaran profesional (Roberts & Pruitt, 2003;Antinluoma et al, 2018;Abdullah, 2009;Kalkan, 2016). Pengikut adalah komponen penting dalam amalan kepimpinan, kerana pengikut membantu amalan kepimpinan melalui interaksi mereka mengikut situasi (Spillane, 2005).…”
Section: Model Kepimpinan Distributifunclassified
“…Komuniti pembelajaran profesional merujuk kepada aktiviti pembangunan profesional berterusan yang dirancang dan dilaksanakan oleh sekolah atau kumpulan yang mempunyai hubungan rapat dengan pihak sekolah (Malaysia, 2014). Contoh komuniti pembelajaran profesional adalah sekolah dan panitia matapelajaran (Abdullah, 2009;dan Kalkan, 2016;Roberts & Pruitt, 2003;Antinluoma et al, 2018). Namun begitu jumlah kajian tentang berkaitan pengaruh kepimpinan distributif terhadap komuniti pembelajaran profesional dalam kalangan pemimpin sekolah menengah di negeri Johor adalah terhad.…”
unclassified
“…Previous Finnish educational studies related to PLCs have mostly been concerned with separate dimensions like leadership (Raasumaa, 2010;Risku and Kanervio, 2011;Tian et al, 2016;Lahtero et al, 2019), culture (Niemi et al, 2014), teacher learning (Ilomäki et al, 2017), teachers' relationships and working environment (Pyhältö et al, 2011), occupational wellbeing (Laine et al, 2018), and co-teaching practices (Ahtiainen et al, 2011). The aim of this multiple-case study of four Finnish schools, based on the results received in an earlier quantitative study (Antinluoma et al, 2018), is to fill the gap and examine the capacities of PLCs. These schools were selected because results from the earlier study indicated that they were ready to operate as PLCs.…”
Section: Introductionmentioning
confidence: 99%